Improving Student Learning in Web Programming through Practical Assessment and Project Exhibitions - Meliana Christianti Johan; Bernard Renaldy Suteja; Rafael Yefta Wijaya; Joshua Christian Benedict; Alfian Febina Sabtuja (Journal of Applied Business and Technology, 2026)
Assessment functions as an effective means to enhance learning and education. Assessment practices should align with course objectives and educational purposes. A well-designed assessment must demonstrate four core attributes: relevance, feasibility, validity, and reliability. In the Basic Web Programming course, traditional methods like assignments and exams often fail to capture students' ability to apply theoretical knowledge in real situations. This study aims to identify key assessment needs and develop better evaluation tools through qualitative needs analysis with 61 first-year Informatics Engineering students via surveys and interviews. The research included four phases: needs identification, instrument development, classroom implementation, and results evaluation. Survey data revealed that 95.7% of students (44 out of 46 respondents) expressed high satisfaction levels (rating 8-10) with course quality, indicating that practical assignments and programming projects significantly enhanced their learning experience. Based on these findings, we designed a new assessment model comprising four components: practical assignments, programming projects, practical exams, and student work exhibitions. The exhibition received 91.3% positive feedback from students, while guest evaluations showed exceptional results with 97.3% expressing high satisfaction and 78.2% giving maximum ratings. Implementation resulted in improved student performance, higher participation rates, and increased motivation. The new tools also supported creativity and teamwork essential in programming education. This study provides valuable insights for educators seeking to enhance learning outcomes through practical assessment strategies meeting students' needs.